2016
DOI: 10.5530/phm.2016.7.20
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Rebamipide Loaded Gastroretentive Alginate Based Mucoadhesive Beads: Formulation & In-vitro, In-vivo Evaluation

Abstract: Introduction: Oral route is the most common and convenient route to deliver the drug. Many oral drug delivery systems were developed to improve drug bio availability; gastro retentive drug delivery system is one of them. Gastroretentive drug delivery system is the system in which a drug can remain in the gastric region for several hours in order to prolong its gastric residence time. The purpose of this work was to develop and evaluate rebamipide loaded gastro retentive alginate based muco adhesive beads. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The increase in the bead size with the increase in the alginate concentration may be ascribed to the increase in the viscosity of the polymer dispersion [26]. These findings were in a good correlation with Kashid et al, who found that there was a significant increase in SA beads size from 0.06±0.02 mm to 0.11±0.014 mm with the increase in the SA amount from 100 mg to 300 mg at 6% CaCl 2 [27].…”
Section: Particle Sizesupporting
confidence: 69%
See 1 more Smart Citation
“…The increase in the bead size with the increase in the alginate concentration may be ascribed to the increase in the viscosity of the polymer dispersion [26]. These findings were in a good correlation with Kashid et al, who found that there was a significant increase in SA beads size from 0.06±0.02 mm to 0.11±0.014 mm with the increase in the SA amount from 100 mg to 300 mg at 6% CaCl 2 [27].…”
Section: Particle Sizesupporting
confidence: 69%
“…There was a significant increase in the maraviroc alginate microspheres mucoadhesion percentage after 4 h from 55± 3.51 to 78± 2.08 with an increase in the drug to polymer ratio from 1:1 to 1:2, respectively [21]. An increase in the concentration of SA resulted in an increase in the amount of free carboxylic group which was responsible for the binding to the sialic acid group of the vaginal mucosa [27].…”
Section: Swelling Indexmentioning
confidence: 99%
“…The FTIR spectra of VerHCl, sodium alginate, VerHCl / sodium alginate physical mixture (1:1 w/w) and VerHCl loaded alginate beads were recorded using (Spectrum Two FTIR spectrometer, Perkin Elmer, USA). The spectra of samples were recorded over the wavelength region of (4000-400 cm −1 ) 21 .…”
Section: Fourier-transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…The diameter of the microspheres cone will be measured and then the angle of repose. 8,9 tan θ =h/r b. Bulk density (BD) and Tapped density (TD):2 g of granules blend was introduced to a measuring cylinder of 100 ml.…”
Section: Micromeritics Studies Of Prepared Microspheresmentioning
confidence: 99%